Neurovascular Interaction Promotes the Morphological and Functional Maturation of Cortical Neurons - Wu, Kun-Wei; Mo, Jia-Lin; Kou, Zeng-Wei; Liu, Qi; Lv, Ling-Ling; Lei, Yu; Sun, Feng-Yan (Frontiers in Cellular Neuroscience, 2017)
Brain microvascular endothelial cells (BMEC) have been found to guide the migration, promote the survival and regulate the differentiation of neural cells. However, whether BMEC promote development and maturation of immature neurons is still unknown. Therefore, in this study, we used a direct endothelium-neuron co-culture system combined with patch clamp recordings and confocal imaging analysis, to investigate the effects of endothelial cells on neuronal morphology and function during development. We found that endothelial cells co-culture or BMEC-conditioned medium (B-CM) promoted neurite outgrowth and spine formation, accelerated electrophysiological development and enhanced synapse function. Moreover, B-CM treatment induced VEGF expression and p38 phosphorylation in the cortical neurons. Through pharmacological analysis, we found that incubation with SU1498, an inhibitor of VEGF receptor, abolished B-CM-induced p-p38 upregulation and suppressed the enhancement of synapse formation and transmission. SB203580, an inhibitor of p38 MAPK also blocked B-CM-mediated synaptic regulation. Together these results clearly reveal that the endothelium-neuron interactions promote morphological and functional maturation of neurons. In addition, neurovascular interaction-mediated promotion of neural network maturation relies on activation of VEGF/Flk-1/p38 MAPK signaling. This study provides novel aspects of endothelium-neuron interactions and novel mechanism of neurovascular crosstalk.